Serial Communication Reliability Testing in Dynalite Lighting Control with Adjustable Voltage Levels - Hadikusuma, Ridwan Satrio; Triyanto, Aripin; Nuryana, Muhammad Risqi (DPTE FT UNY, 2025)
This research presents the reliability testing of serial communication in Dynalite lighting control systems with adjustable voltage levels. The study began with the design and implementation of a DALI-based topology, followed by practical installation and measurement of output voltages at different control levels (10%, 20%, 40%, 80%, and 100%). The results confirmed that the output voltage correlated proportionally with the configured percentage level, demonstrating stable driver performance in regulating lamp brightness. Furthermore, comparative testing at different baud rates, namely 9600bps and 115200bps, was conducted to evaluate communication stability. The findings revealed that 9600bps provided higher reliability and minimal error, while 115200bps offered faster response but with a higher risk of instability. These results emphasize the importance of selecting appropriate voltage and baud rate configurations to ensure both efficiency and robustness in lighting control systems.